f-¹(x)=![\frac{2-7x}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B2-7x%7D%7Bx%2B2%7D)
Answer:
Solution given:
f(x)=![\frac{-2x+2}{x+7}](https://tex.z-dn.net/?f=%5Cfrac%7B-2x%2B2%7D%7Bx%2B7%7D)
Let f(x)=y
y=![\frac{-2x+2}{x+7}](https://tex.z-dn.net/?f=%5Cfrac%7B-2x%2B2%7D%7Bx%2B7%7D)
Interchanging role of x and y
x=![\frac{-2y+2}{y+7}](https://tex.z-dn.net/?f=%5Cfrac%7B-2y%2B2%7D%7By%2B7%7D)
doing crisscrossed multiplication
x(y+7)=-2y+2
now solve it:
xy+7x=-2y+2
keep like terms in one side
xy+2y=2-7x
take common
y(x+2)=2-7x
make a value of y
y=![\frac{2-7x}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B2-7x%7D%7Bx%2B2%7D)
So,
f-¹(x)=![\frac{2-7x}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B2-7x%7D%7Bx%2B2%7D)
A = 15 a = athena, s = samantha, b = bonus points
s = b + a
s = b + 15